2017
DOI: 10.5603/kp.a2016.0096
|View full text |Cite
|
Sign up to set email alerts
|

Individualised renal artery denervation improves blood pressure control in Kazakhstani patients with resistant hypertension

Abstract: In this population RAD resulted in statistically and clinically significant blood pressure reduction at 12 months with minimal adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Also, similar studies have shown possible alterations of insulin sensitivity mediated by RDN. More specifically, Aripov et al [ 40 ], in a study assessing RDN’s effect in 63 patients with resistant hypertension, noted a significant reduction of the homeostasis model assessment-insulin resistance (HOMA-IR) index, which was significantly reduced by a mean of 0.5 at 12 months.…”
Section: Renal Denervation and Glycemic Control: Preclinical And Clin...mentioning
confidence: 99%
“…Also, similar studies have shown possible alterations of insulin sensitivity mediated by RDN. More specifically, Aripov et al [ 40 ], in a study assessing RDN’s effect in 63 patients with resistant hypertension, noted a significant reduction of the homeostasis model assessment-insulin resistance (HOMA-IR) index, which was significantly reduced by a mean of 0.5 at 12 months.…”
Section: Renal Denervation and Glycemic Control: Preclinical And Clin...mentioning
confidence: 99%